An investigation on the practicability of usage based insurance and telematics to the Zimbabwean motor insurance industry. - Mundowa, Matthew Tanaka (Midlands State University, 2017)
The research sought to investigate the practicability of introducing usage based insurance to the Zimbabwean motor insurance industry so as to address short comings of the traditional rating method. Literature was reviewed on the different UBI programs, telematics, the shortfalls of the traditional rating method, benefits of UBI, how to implement it in to practice, the challenges with implementing it in the Zimbabwean context and a case study of Discovery Insure, a South African insurance company. The targeted population for this study where twenty short-term insurance companies registered with the Insurance and Pensions Commission (IPEC). From the target population the researcher obtained a sample size of fourteen insurance companies. These fourteen companies were chosen at random, using simple random sampling. The researcher administered questionnaires and used personal interviews in collecting information related to the research from respondents. The results obtained indicated that the majority of insurers were aware of UBI and where willing to implement UBI in the near future but less prepared to because of the high cost associated with putting the program into practice amongst other issues. The data collected was presented using tables, pie charts and bar graphs. The study recommends that insurance companies should come together and invite companies from abroad that have experience using UBI and host workshops or conferences that will help as a guide on ways to successfully implement the program. Other recommendations included forming partnerships with companies with the right infrastructure such as Econet, Involving the government as well as carrying out insurance awareness campaigns for the public due to the lack of knowledge and appreciation of insurance in general that lies in the with in the public, as this will have an impact on UBI uptake if implemented, as well as improve the performance of existing products.